2001
DOI: 10.1161/01.cir.104.2.137
|View full text |Cite
|
Sign up to set email alerts
|

Aldosterone Induces Angiotensin-Converting-Enzyme Gene Expression in Cultured Neonatal Rat Cardiocytes

Abstract: Aldosterone upregulates ACE mRNA expression, which is blocked by spironolactone in neonatal rat cardiocytes. Thus, spironolactone may suppress the progression of heart failure by blocking the effects of aldosterone and angiotensin II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
124
0
3

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(134 citation statements)
references
References 23 publications
7
124
0
3
Order By: Relevance
“…Aldosterone, as already mentioned, increases tissue ACE activity 45 and upregulates angiotensin receptors. 40 This suggests the potential for a vicious cycle in which Ang II, through the AT 1 receptor, stimulates the production of aldosterone, which, in turn, leads to an increase in tissue ACE activity, an additional increase in Ang II, and, therefore, an additional elevation in aldosterone levels.…”
Section: Integrative Molecular Physiology Of Vascular Effects Of Aldomentioning
confidence: 59%
See 1 more Smart Citation
“…Aldosterone, as already mentioned, increases tissue ACE activity 45 and upregulates angiotensin receptors. 40 This suggests the potential for a vicious cycle in which Ang II, through the AT 1 receptor, stimulates the production of aldosterone, which, in turn, leads to an increase in tissue ACE activity, an additional increase in Ang II, and, therefore, an additional elevation in aldosterone levels.…”
Section: Integrative Molecular Physiology Of Vascular Effects Of Aldomentioning
confidence: 59%
“…[42][43][44] More recently, it has been demonstrated that aldosterone upregulates components of the renin-angiotensin system, specifically angiotensin-converting enzyme (ACE), resulting in increased local generation of Ang II (Figure 1). 45 Furthermore, aldosterone exerts direct effects on signaling in VSMCs, upregulating mitogen-activated protein (MAP) kinases. 46 -48 In salt-loaded stroke-prone spontaneously hypertensive rats (SHRSPs) fed high-(4.2%), normal-(0.28%), or low-salt (0.03%) diets with or without eplerenone, BP rise was prevented by eplerenone in the salt-loaded rats, with little effect on control and low-salt SHRSPs.…”
Section: Schiffrinmentioning
confidence: 99%
“…A previous study indicated the existence of a positive feedback pathway from MR activation to ACE within the local cardiac renin-angiotensin-aldosterone system. 37 These results suggested the existence and the importance of local tissue regulation of the rennin-angiotensin-aldosterone system in the atrium. Further study is needed to clarify the mechanism of MR activation in DS rats.…”
Section: Discussionmentioning
confidence: 87%
“…Ang II induces aldosterone synthesis through stimulation of AT1 (Ang II type 1) receptors in the adrenal cortex. Aldosterone increases tissue ACE (angiotensin converting enzyme) activity and up-regulates angiotensin receptors [62], which suggests the existence of a vicious cycle that may potentiate the effect of the RAAS.…”
Section: Part II -Role Of the Renin-angiotensin-aldosterone System Onmentioning
confidence: 99%